Answer:
4.25
Explanation:
You're having to use the method P.E.M.D.A.S (Parenthesis, Exponents, Multiplication, Division, Adding and Subtracting) each one going in order.
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
17-5*(2*x-9)-((6*x-10)+4)=0
(17 - 5 • (2x - 9)) - (6x - 6) = 0
3.1 Pull out like factors :
68 - 16x = -4 • (4x - 17)
-4 • (4x - 17) = 0
4.1 Solve : -4 = 0
A a non-zero constant never equals zero.
4.2 Solve : 4x-17 = 0
Add 17 to both sides of the equation :
4x = 17
Divide both sides of the equation by 4:
x = 17/4 = 4.250
x = 17/4 = 4.250